2019
DOI: 10.1097/01.reo.0000000000000150
|View full text |Cite
|
Sign up to set email alerts
|

Interventions Addressing Neurodevelopmental Delay in Young Children Infected With and Exposed to HIV: A Scoping Review

Abstract: Background: Neurodevelopmental delays have been documented in children living with and infected by the human immunodeficiency virus (HIV). Early childhood stimulation programs can positively impact neurodevelopmental outcomes and have a far-reaching effect beyond childhood. Objective: To conduct a scoping review mapping evidence describing interventions aimed at mitigating or preventing neurodevelopmental delays resulting from exposure to or infection w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Interventions aimed at improving developmental outcomes in HEI children have been employed but differ widely in their approach (Strehlau, van Aswegen, & Potterton, 2019) and effectiveness (Sherr, Croome, Bradshaw, & Parra Castaneda, 2014). Programmes aimed at improving childhood developmental outcomes have shown substantial and sustainable results (Engle et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions aimed at improving developmental outcomes in HEI children have been employed but differ widely in their approach (Strehlau, van Aswegen, & Potterton, 2019) and effectiveness (Sherr, Croome, Bradshaw, & Parra Castaneda, 2014). Programmes aimed at improving childhood developmental outcomes have shown substantial and sustainable results (Engle et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Childhood HIV management programmes do not, however, uniformly emphasize developmental stimulation nor screening for developmental delays. Reported developmental interventions utilized for HIV‐infected children differ widely in their approach, duration, intensity and timing (Strehlau, van Aswegen, & Potterton, 2019). Consequently, results may not be comparable.…”
Section: Introductionmentioning
confidence: 99%
“…There are emerging physical challenges that PHIVA face, specifically with regard to growth failure, delayed puberty, and cardiac and lung dysfunction. 4 , 5 Numerous studies have highlighted the detrimental effects of perinatal HIV on both birth weight and developmental milestones, 6 , 7 leading to persistent growth issues that extend into adolescence. 5 An analysis of data from 8737 PHIVA found that by age 10, 39% of female PHIVA and 34% of male PHIVA experienced stunted growth.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive di culties may also play a role in the complex skills needed to avoid risky behaviour, such as negotiating safety, self-con dence to avoid drug and alcohol misuse, and strategic planning and coping to navigate social challenges. However, cognitive functioning of ALHIV in Sub-Saharan Africa remains a neglected area of research and service provision (17,18). This is compounded by the limited availability of resources (both technical and nancial) required to administer comprehensive neuropsychological assessment batteries to identify functioning levels and refer to services where available.…”
Section: Introductionmentioning
confidence: 99%